The Letters of Edward Fitzgerald, Volume 3 : 1867-1876 - FitzGerald, Edward, 1809-1883 (Princeton legacy library., 2014)
Bringing together more than a thousand unpublished letters as well as all the widely scattered published ones, these four volumes represent the first attempt at a complete edition of the letters of Edward Fitzgerald (1809-1883).